Defining Canada’s Extended Continental Shelves - Verhoef, Jacob; Mosher, David; Forbes, Steve (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2011)
SUMMARY Article 76 of the United Nations Convention on the Law of the Sea provides a process to delineate Canada’s continental shelf where it extends beyond 200 nautical miles. After ratification of the Convention in 2003, Canada started a program to acquire and analyze the scientific data required for a submission to the Commission on the limits of the continental shelf. This submission will assist Canada in defining the outer limits of its continental shelf, thereby determining, with precision, the area where Canada may exercise its sovereign rights over natural resources. This paper outlines the scope of that program and summarizes the scientific activities to date. Data collection along the Atlantic margin was completed according to plan and the data are presently being analyzed. Data collection in the Arctic has been challenging because of ice and weather conditions, and several innovative solutions were implemented to collect seismic and bathymetry data using ice-breakers and large ice camps. The narrow Pacific margin provides no clear prospects for an extended continental shelf. Overall, the program is on schedule to meet the December 2013 deadline for submission to the Commission.